Քաղաքային թատերական համալիրի ճարտարապետությունը Թեհրանում - Սառա Մալեքմոհամմադի (ՀՀ ԳԱԱ հրատ.)
Здание Тегеранского театра является архитектурным шедевром и одним из самых важных театральных комплексов в Иране на сегодняшний день.The City theater complex in Tehran is one of the architectural masterpieces and it’s currently the most important theater complex in Iran.
Keywords: Architecture; Dramatic representation; The Theater; Language and Literature